Experiential Learning Research Trends Through Bibliometric Analysis 2019-2023 - Ainiyah, Maf Ulatul; Tjipto Subroto, Waspodo; Hakim, Luqman (Sumber Belajar Sejahtera, 2025)
In the evolving digital era, Experiential Learning (EL) emerges as a vital active learning method, fostering the development of 21st-century skills and student-centered education. This study conducts a bibliometric analysis using the Scopus database and VOSviewer software to systematically map EL research trends from 2019-2023. Analyzing 1,012 documents, findings reveal a significant increase in EL publications, rising from 125 in 2019 to 300 in 2023, largely led by global universities and scientific articles as the primary format. Key research trends include technology integration (software, AI, big data) and the complex relationship between EL and entrepreneurship education. This underscores the increasing importance of EL in contemporary education for preparing individuals to face real-world challenges